Association between Clinical Characteristics and Laboratory Findings with Outcome of Hospitalized COVID-19 Patients: A Report from Northeast Iran. (10th February 2021) - Sobhani, Sahar; Aryan, Reihaneh; Kalantari, Elham; Soltani, Salman; Malek, Nafise; Pirzadeh, Parisa; Yarahmadi, Amir; Aghaee, Atena
Abstract : Coronavirus disease 2019 (COVID-19) was first discovered in December 2019 in China and has rapidly spread worldwide. Clinical characteristics, laboratory findings, and their association with the outcome of patients with COVID-19 can be decisive in management and early diagnosis. Data were obtained retrospectively from medical records of 397 hospitalized COVID-19 patients between February and May 2020 in Imam Reza Hospital, northeast Iran. Clinical and laboratory features were evaluated among survivors and nonsurvivors. The correlation between variables and duration of hospitalization and admission to the intensive care unit (ICU) was determined. Male sex, age, hospitalization duration, and admission to ICU were significantly related to mortality rate. Headache was a more common feature in patients who survived (p = 0.017 ). It was also related to a shorter stay in the hospital (p = 0.032 ) as opposed to patients who experienced chest pain (p = 0.033 ). Decreased levels of consciousness and dyspnea were statistically more frequent in nonsurvivors (p = 0.003 and p = 0.011, respectively). Baseline white blood cell (WBC) count, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) were significantly higher in nonsurvivors (p < 0.001 ). Patients with higher WBC and CRP levels were more likely to be admitted to ICU (p = 0.009 and p = 0.001, respectively). Evaluating clinical and laboratory features can help clinicians find ways for risk stratifying patients and even make predictive tools. Chest pain, decreased level of consciousness, dyspnea, and increased CRP and WBC levels seem to be the most potent predictors of severe prognosis.